‘It never seems to stop’ Six high school students’ experiences of information overload - Mira Grønning Aadland; Jannica Heinström (Information Research: An International Electronic Journal)
Introduction. The paper explores high school students' experiences of information overload in the context of their studies, investigating its causes and how they manage it.